1989
DOI: 10.1002/actp.1989.010400508
|View full text |Cite
|
Sign up to set email alerts
|

Synthese, Charakterisierung und Symplexbildung von Polyampholyten aus ungesättigten Dicarbonsäure‐ und Allylaminderivaten. 2. Mitt.: Spektroskopische Untersuchungen an Polymeren aus Maleinsäure und Allylaminderivaten

Abstract: 331Besides the surface activity of the amino resins used, the electrostatic interactions between the protonated amino resin and the negatively charged organic phase can be considered as driving force. Thereby the reaction rate of the polycondensation in the boundary phase is increased contrary to the volume phase with the result of capsule wall formation.These conceptions are supported by the fact t h a t in the presence of other non-reactive tensides no microcapsules will be formed. These tensides occupy the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Numerous studies on random polyampholytes have been reported by various groups, for example those of Candau [2][3][4][5][6][7] and McCormick [8][9][10][11]. Hahn et al prepared several alternating polyampholytes [12][13][14][15][16] and characterized their aqueous solution properties, while the synthesis and characterization of diblock polyampholytes was not accomplished until 1970s [17][18][19]. Such a synthesis requires sequential monomer addition under living polymerization conditions, usually with protected monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on random polyampholytes have been reported by various groups, for example those of Candau [2][3][4][5][6][7] and McCormick [8][9][10][11]. Hahn et al prepared several alternating polyampholytes [12][13][14][15][16] and characterized their aqueous solution properties, while the synthesis and characterization of diblock polyampholytes was not accomplished until 1970s [17][18][19]. Such a synthesis requires sequential monomer addition under living polymerization conditions, usually with protected monomers.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Noteworthy, cyclocopolymerization of allylamine, diallylamine and Nmethyldiallylamine with maleic acid was occasionally reported to yield regular poly(ampholyte)s systems in the form of alternating copolymers. [6][7][8][9][10] This is an attractive approach to well-defined poly(ampholyte)s which generally must be prepared by the polymerization of specially designed monomers, [11][12][13][14] or by multistep synthesis via reactive precursor polymers. [15][16][17] Within other interesting potential uses, poly(ampholyte)s may serve as models or mimics of proteins, especially when bearing hydrophobic fragments that render them amphiphilic.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable literature on the synthesis and aqueous solution properties of random linear zwitterionic copolymers. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The synthesis and characterization of diblock polyampholytes were not accomplished until the 1970s. [20][21][22] Such synthesis requires sequential monomer addition under living polymerization conditions, usually with protected monomers.…”
Section: Introductionmentioning
confidence: 99%